2011
DOI: 10.1007/s00348-011-1248-2
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous assessment of peak-locking and CCD readout errors through a multiple Δt strategy

Abstract: The multiple Dt strategy is an inexpensive procedure that can be implemented with any usual particle image velocimetry (PIV) set up. The only requirement is acquiring different series of PIV image pairs, setting a different time between laser pulses for each series. With this additional information, robust procedures for error assessment are possible. Within this strategy, this paper offers new discoveries that correct and complement previous works by the authors. Nogueira et al. (Meas Sci Technol 20-7:074001… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…However, charge transfer efficiency is not identical for the first and for the second image capture readout, leading to a residual differential bias in the digitally registered particle displacement. This bias error has already been observed and its magnitude evaluated for particular cases by Nogueira et al (2009) and Legrand et al (2010Legrand et al ( , 2011.…”
Section: Readout Smearingsupporting
confidence: 55%
See 2 more Smart Citations
“…However, charge transfer efficiency is not identical for the first and for the second image capture readout, leading to a residual differential bias in the digitally registered particle displacement. This bias error has already been observed and its magnitude evaluated for particular cases by Nogueira et al (2009) and Legrand et al (2010Legrand et al ( , 2011.…”
Section: Readout Smearingsupporting
confidence: 55%
“…The conclusion leads to highlighting the importance of avoiding spurious sources of light and the use of interferometric filters as means to reduce measurement errors. Nogueira et al (2009) as well as Legrand et al (2011) have already discussed the feasibility of a multiple t strategy designed to evaluate the bias error, including the possibility of correcting it under certain circumstances. However, the present work sheds light on the physical phenomenon of particle image smearing, and predicts the magnitude and whether or not some readout displacement bias error would be present in the measurements.…”
Section: Displacement Bias Error In Real Piv Ccd Camerasmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of methods have been proposed to exploit multiple images in the form of successive pairs of PIV images provided by current highspeed PIV cameras. These approaches improve the double-pulsed PIV measurements by using images at multiple times to optimize parameters (Legrand et al 2012), averaging over successive measurements assuming constant velocity (A. Sciacchitano, F. Scarano & B. Wieneke, private communication) or using adjustable time delays between double pulses (Hain & Kähler 2007). …”
Section: Time-resolved Pivmentioning
confidence: 99%
“…The discussion above shows that the problem of peak locking errors due to small particle image diameters, especially in the case of CMOS cameras for high-speed PIV measurements, is still unsolved. In such a situation, a continuous development in the approaches based on multiple Δt image acquisition (Nogueira et al 2009, Nogueira et al 2011, Legrand et al 2012, Legrand et al 2018 has shown a high potential in peak-locking error quantification and correction, Δt being a time separation between two frames in PIV. Using a set of different Δt's for the same flow measurement allows for segregating the errors that scale with Δt (e.g.…”
Section: Introductionmentioning
confidence: 99%